Google hacks - Dornfest, Rael (Hacks series., 2006)
"Here's a sampling of the features of this book: search Google over IM with a Google Talk bot; build a customized Google Map and add it to your own Web site; cover your searching tracks and take back your browsing privacy; turn any Google query into an RSS feed that you can monitor in Google Reader or the newsreader of your choice; keep tabs on blogs in new, useful ways; turn Gmail into an external hard drive for Windows, Mac, or Linux, beef up your Web pages with search, ads, news feeds, and more; and program Google with the Google API and your favorite language."--Jacket.